Protection of Personal Data in Computerized Accounting Programs (European Journal of Formal Sciences and Engineering, 2024)
One of the most vital accounting activities that businesses and organizations engage in is the essential planning and meticulous control of personal data collection and distribution. This task is particularly important in today's rapidly evolving landscape, where the nature of data management is constantly changing. The swift growth of new and innovative computer technologies has significantly influenced and transformed this crucial area of accounting practice. Computerized accounting programs are comprised of advanced and sophisticated software that effectively automates the entire accounting cycle, which in turn enhances both efficiency and accuracy in various financial record-keeping and reporting processes. As these advanced technologies continue to develop at an astounding pace, they not only streamline operations but also ensure compliance with ever-evolving regulations and improve overall data security. This results in the safeguarding of sensitive information, making it an indispensable component of modern accounting systems. In this study, a detailed research was conducted on the protection of personal data in computerized accounting programs.
Keywords: computerized accounting, personal data protection, data security